Ujednolicony program analizy statystycznej ASTA w sterowaniu procesami przemysłowymi na elektronicznych maszynach cyfrowych - Kulik, Czesław (Wydział Prawa i Administracji UAM, 1969)
The paper presents an exemplary scheme of the uniform program of ASTA statistical analysis. It may be applied in the investigation of productive processes steered by means of modern computers. The paper deals with basic terms and describes such aspects as: 1. the productive process, 2. information, 3. the scheme of control and steering, 4. the description of continuous and impulsive systems, 5. the structure of the theoretical model, 6. the analysis of structural features, 7. economic data, 8. the program of statistical analysis. The last paragraph of the paper includes the scheme (with a diagram and description) of the ASTA universal program embracing a wide range of problems connected with the steering and control of productive processes.
The Uniform Program of ASTA Statistical Analysis in the Steering of Industrial Processes on Electronic Computers